Perceptions of an Empowering and Disempowering Motivational Climate, Psychobiosocial States and Athlete Burnout in Young Football Players - Lappi, Sanni (2025)
Athlete burnout is a growing concern in youth sport. Athlete burnout can have detrimental effects for both mental and physical well-being and eventually, lead to dropping out from sports altogether. As sport and exercise are important for both individual and societal well-being, it is important to understand how burnout develops and how it can be prevented.